A sensitive and scalable microsatellite instability assay to diagnose constitutional mismatch repair deficiency by sequencing of peripheral blood leukocytes. Issue 5 (6th March 2019) - Gallon, Richard; Mühlegger, Barbara; Wenzel, Sören‐Sebastian; Sheth, Harsh; Hayes, Christine; Aretz, Stefan; Dahan, Karin; Foulkes, William; Kratz, Christian P.; Ripperger, Tim; Azizi, Amedeo A.; Baris Feldman, Hagit; et al.
Abstract: Constitutional mismatch repair deficiency (CMMRD) is caused by germline pathogenic variants in both alleles of a mismatch repair gene. Patients have an exceptionally high risk of numerous pediatric malignancies and benefit from surveillance and adjusted treatment. The diversity of its manifestation, and ambiguous genotyping results, particularly from PMS2, can complicate diagnosis and preclude timely patient management. Assessment of low‐level microsatellite instability in nonneoplastic tissues can detect CMMRD, but current techniques are laborious or of limited sensitivity. Here, we present a simple, scalable CMMRD diagnostic assay. It uses sequencing and molecular barcodes to detect low‐frequency microsatellite variants in peripheral blood leukocytes and classifies samples using variant frequencies. We tested 30 samples from 26 genetically‐confirmed CMMRD patients, and samples from 94 controls and 40 Lynch syndrome patients. All samples were correctly classified, except one from a CMMRD patient recovering from aplasia. However, additional samples from this same patient tested positive for CMMRD. The assay also confirmed CMMRD in six suspected patients. The assay is suitable for both rapid CMMRD diagnosis within clinical decision windows and scalable screening of at‐risk populations. Its deployment will improve patient care, and better define the prevalence and phenotype of this likely underreported cancer syndrome. Abstract : A simple and scalable sequencing assay, that assesses microsatellite instability (MSI) in the genomic DNA of peripheral blood leukocytes (PBLs), can detect constitutional mismatch repair deficiency (CMMRD) with 97% sensitivity and 100% specificity, including samples from patients with hypomorphic PMS2 variants (†). The assay also discriminates between patients with monoallelic pathogenic mismatch repair variants (Lynch syndrome) and biallelic pathogenic mismatch repair variants (CMMRD). The one misclassified sample was from an aplastic patient (§), who was correctly diagnosed by analyzing additional samples.